2016
DOI: 10.1111/1346-8138.13252
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of interleukin‐18‐binding protein isoform a: Clinical association with inflammation and pulmonary hypertension in systemic sclerosis

Abstract: Systemic sclerosis (SSc) is a chronic autoimmune inflammatory disease characterized by extensive tissue fibrosis and various vascular complications. A wealth of evidence suggests the substantial contribution of pro-inflammatory cytokines to the development of SSc, but the role of interleukin (IL)-18 signaling in this disease still remains elusive. To address this issue, we herein determined serum levels of IL-18-binding protein isoform a (IL-18BPa), a soluble decoy receptor for IL-18, by enzyme-linked immunoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…[25,26] Serum IL-18 levels significantly increase during hypoxia caused by acute lung injury [27] and elevated IL-18 levels have been associated with the presence of systemic inflammation. [28] Our results showed that APACHE II was significantly lower in ARDS patients with high level of serum IL-18 than that with low IL-18. APACHE II was also significantly lower in the non-survival group than that in survival group.…”
Section: Discussionmentioning
confidence: 67%
“…[25,26] Serum IL-18 levels significantly increase during hypoxia caused by acute lung injury [27] and elevated IL-18 levels have been associated with the presence of systemic inflammation. [28] Our results showed that APACHE II was significantly lower in ARDS patients with high level of serum IL-18 than that with low IL-18. APACHE II was also significantly lower in the non-survival group than that in survival group.…”
Section: Discussionmentioning
confidence: 67%
“…Realtime three-dimensional cardiac ultrasound effectively overcomes the limit of application range of two-dimensional ultrasound in clinical, and can directly make quantitative measurement of actual ventricular volume. This measurement has higher accurate and convenient measurement of irregular geometrical ventricular volume which can satisfy with accurate evaluation of right ventricular functions in clinical [11][12][13].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, interleukin-18 (IL-18) Receptor 1 (IL-18R1) is a miR-26 target expressed by WBCs. Previous publications showed that IL-18 levels are altered in SSc patients [39,40] and that there is a positive correlation between serum IL-18 binding protein (IL-18BPa) levels and right ventricular systolic pressure [39].…”
Section: Discussionmentioning
confidence: 99%